TIMP-3 suppression induces choroidal neovascularization by moderating the polarization of macrophages in age-related macular degeneration. (February 2019) - Cheng, Ying; Cheng, Tongjie; Qu, Yi
Highlights: TIMP-3 suppression could alter the macrophage polarization to M2 type in bone marrow-derived macrophages. siR-TIMP-3 regulates macrophage polarization to a more pro-angiogenic subtype in RPE/Choroidal tissues with CNV animal model. OCTA is effective to observe the CNV lesion in BN rat eye, indicating the absence of TIMP-3 might accelerate the growth of CNV lesions. Abstract: Purpose: To investigate the role of tissue inhibitor of metalloproteinases–3 (TIMP-3) as a key moderator of macrophage polarization in choroidal neovascularization (CNV) lesions of model mice and in bone marrow-derived macrophage (BMDM). Method: We used siR-TIMP-3 to transfect BMDM and gave an intravitreal injection of siR-TIMP-3 to laser-induced CNV mice model, real time-PCR and western blot were applied for detecting the expressions of TIMP-3 and macrophages' biomarker. Besides, CNV lesions in different treatment groups of animal model were examined by the optical coherence tomography angiography (OCTA). Results: Our experimental data showed that lack of TIMP-3 stimulated M2 polarization proved by real time-PCR and western blot in BMDMs and CNV mice model. Moreover, intravitreal injection of siR-TIMP-3 accelerated CNV formation using OCTA, which indicated that TIMP-3 suppression is related to pro-angiogenesis of M2 macrophage. Conclusion: We showed that the absence of TIMP-3 leads to a more pro-angiogenic microenvironment, playing a key role in CNV formation by positively modulating M2 polarization. The role of TIMP-3 in the regulating inflammation and novel therapeutic target of nAMD needs to be further studied.